CHRONIC HEART FAILURE: PATHOPHYSIOLOGY, CLINICAL MANIFESTATIONS AND CONTEMPORARY MANAGEMENT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
Chronic Heart Failure (CHF) is a complex clinical syndrome resulting from structural or functional impairment of ventricular filling or ejection of blood. It represents a leading cause of hospitalization and mortality worldwide. CHF is characterized by neurohormonal activation, reduced cardiac output, and systemic congestion. This paper examines the epidemiology, pathophysiology, classification, clinical presentation, diagnostic strategies, complications, and modern treatment approaches of chronic heart failure following the IMRAD structure.